2015
DOI: 10.3324/haematol.2014.106468
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis specific loss of Cdk2 and Cdk4 results in increased erythrocyte size and delayed platelet recovery following stress

Abstract: ABSTRACTcrossed with Cdk4 +/-mice, 10 and the resulting heterozygous offspring Cdk2 +/fl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Notably, no evident abnormalities were observed in HSCs from CDK2-deficient mice, indicating that other molecules (such as the CDK1-cyclin E complex as reasoned in the following section) may compensate for the loss of CDK2 [25]. Although mice lacking either CDK2 or CDK4 are viable, double knockout mutants for these two molecules are embryonically lethal at around E15 due to heart defects, indicating that CDK2 and CDK4 play synergistic roles during development [24,26].…”
Section: Cdk2mentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, no evident abnormalities were observed in HSCs from CDK2-deficient mice, indicating that other molecules (such as the CDK1-cyclin E complex as reasoned in the following section) may compensate for the loss of CDK2 [25]. Although mice lacking either CDK2 or CDK4 are viable, double knockout mutants for these two molecules are embryonically lethal at around E15 due to heart defects, indicating that CDK2 and CDK4 play synergistic roles during development [24,26].…”
Section: Cdk2mentioning
confidence: 96%
“…CDK2-deficient mice are viable and have a life span of more than 2 years, suggesting that CDK2 is dispensable for the proliferation and survival of most somatic cell types. However, while CDK2 mutant mice are overtly normal, they are sterile, as CDK2 has been shown to be essential for the completion of prophase I during meiotic cell division in male germ cells [24]. Notably, no evident abnormalities were observed in HSCs from CDK2-deficient mice, indicating that other molecules (such as the CDK1-cyclin E complex as reasoned in the following section) may compensate for the loss of CDK2 [25].…”
Section: Cdk2mentioning
confidence: 98%
“…34 Consistent with this theory, several cell cycle proteins that control the G1-S transition, such as E2F4, [35][36][37] Cdk4/Cdk6, 2 cyclin D3, 38 and Cdk2/Cdk4, 20 play critical roles in the regulation of erythrocyte size and numbers. Erythroblasts lacking cyclin D3 underwent reduced number of cell divisions during terminal differentiation resulting in a dramatic 40% increase in erythrocyte MCV and 38% decrease in erythrocyte counts in the peripheral blood of cyclin D3 ¡/¡ mice.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, hematopoiesis was shown to be affected in mice with a combined deficiency of CDK2 and CDK4 [18]. Interestingly, the combined deficiency of these cyclin-dependent kinases resulted in increased erythrocyte cell volume [18].…”
Section: +mentioning
confidence: 99%
“…Interestingly, the combined deficiency of these cyclin-dependent kinases resulted in increased erythrocyte cell volume [18]. The CDK4 inhibitors used in this study are chemically unrelated compounds which have previously been shown to potently inhibit CDK4 kinase activity.…”
Section: +mentioning
confidence: 99%